Elderly and drugs: risks and necessity of rational use - André de Oliveira Baldoni; Farah Maria Drumond Chequer; Elisa Raquel Anastácio Ferraz; Danielle Palma de Oliveira; Leonardo Régis Leira Pereira; Daniel Junqueira Dorta (Universidade de São Paulo, 2010)
In recent decades, the world has undergone a demographic transformation with a rapid growth of the elderly population, resulting in an increased demand for funds to maintain their health and drug consumption. Pharmacokinetic and pharmacodynamic changes occurring in the elderly can interfere directly in the adverse effects of drugs and increase the risk of intoxication. In addition, there are external factors interfering with the pharmacotherapy of the elderly, such as inappropriate use and the lack of access to information. Many therapeutic classes of drugs should be used with caution or avoided in the elderly population, such as anti-inflammatory and some anti-hypertensive drugs, diuretics and digitalis. If not managed carefully, these medicines can affect the safety and quality of life in the elderly. Thus, the aim of this review was to identify drugs that should be used with caution in elderly patients in order to avoid intoxication and/or adverse drug events. Durante as últimas décadas, o mundo passou por uma transformação demográfica, com um rápido crescimento da população idosa e, portanto, tanto a demanda para a manutenção da saúde deste grupo populacional, quanto o consumo de medicamentos estão aumentando. Ainda, as mudanças farmacocinéticas e farmacodinâmicas que ocorrem em idosos podem interferir diretamente nos efeitos adversos dos medicamentos e aumentar o risco de intoxicação. Além disso, há fatores externos que interferem na farmacoterapia dos idosos, tais como o uso inadequado e a falta de acesso à informação. Existem várias classes terapêuticas de medicamentos que devem ser utilizados com cautela ou evitados na população idosa, tais como antiinflamatórios, alguns anti-hipertensivos, diuréticos, digitálicos entre outros. Estes medicamentos, se não forem utilizados com cuidado, podem afetar a qualidade de vida e a segurança desta população. Assim, este trabalho visa identificar medicamentos que devem ser utilizados com cuidado em pacientes idosos para evitar intoxicações e/ou eventos adversos aos medicamentos.